Use of sludge ash from drinking water treatment plant in hydraulic mortars (2019)
The present study investigated the use of sludge ash from water treatment plants as supplementary cementing material, elaborating hydraulic mortars with different levels of cement replacement by sludge ash (10 wt% and 30 wt%) and different temperatures of calcination (600 °C and 800 °C). Characterization of sludge ash and mortars includes XRF, XRD, particle size distribution by laser diffraction, compressive strength, and SEM-EDS. The results show that SiO2, Al2O3, and Fe2O3 compose 90 % of the sludge ash, and it has potential pozzolanic activity. It is evidenced that there is a significant influence of the variable ratio of sludge ash:cement in the compressive strength of the mortar cubes over other variables. Overall, this study showed that the sludge ash could be considered as a viable and sustainable alternative for the construction sector. Despite the benefits of the suggested replacement, the presence of amorphous SiO2 requires a review of long-time chemical behavior.